(untitled) (Agroindustrial Science, 2023)
The objective was to determine the response of three strawberrry varieties (Fragaria x ananassa Duch.) to the aplication of two plant growth regulators: indol acetic acid (IAA) and 6-Benzyl aminopurine (BAP) added to Murashige & Skoog médium in strawberry micropropagation. The complete randomized block design was used and three strawberry varieties ‘Aromas’, ‘Albion’ and ‘Camarosa’ were considered as trials. MS medium for shoot regeneration in initial stage was supplemented with BAP 0.5 mgL-1 and IAA 0.6 mgL-1. Shoot proliferation MS medium was supplemented with BAP 0.5 mgL-1 in multiplication stage and MS medium hormone free was used for rooting induction. It was determined that after 32 days of cultivation the combination of IAA and BAP significantly affected shoot regeneration of apical shoot tips of three strawberry varieties. The greatest effect was caused on ‘Camarosa’. In addition, results on shoot multiplication using BAP indicated that ‘Albion’ performed better in shoot proliferation in terms of shoots per explants reaching 2.51 compared to ‘Camarosa’ and ‘Aromas’ with significant differences. However rooting medium with no growth regulators improves root development with best response of ‘Camarosa’ root length reaching 4.76 cm.